Kemampuan Berbahasa Pada Anak Autis dan Pengaruhnya terhadap Interaksi Sosial: Sebuah Kajian Literatur Sistematis (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Language skills are an important aspect that needs to be considered in children's development because they play a role in their social interaction skills. In general, children usually develop language skills naturally. However, this process may take place differently in children with autism due to disorders in their nervous system. Previous research has revealed variations in the development of autistic children's language skills and the efforts that can be made to help improve their language skills. Therefore, this study aimed to determine the language development of children with autism and analyse the efforts that have been made to improve their language skills through a systematic review. The search method used four electronic databases, namely Sinta, Semantic Scholar, Crossref, and Google Scholar, following the PRISMA Protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for the 2019-2024 publication period. From a total of 54 articles identified, 15 articles met the inclusion and exclusion criteria. The results showed that autistic children tend to experience barriers in language development, especially in the early stages of development. These barriers vary between children. Therefore, positive support from the environment, implementation of practical strategies, and various therapies are needed to achieve optimal language skills in autistic children. It is hoped that this study can provide valuable input for developing more effective and targeted interventions.